2017
DOI: 10.1371/journal.pone.0178319
|View full text |Cite
|
Sign up to set email alerts
|

Greater HbA1c variability is associated with increased cardiovascular events in type 2 diabetes patients with preserved renal function, but not in moderate to advanced chronic kidney disease

Abstract: Emerging evidence suggests that glycemic variability may be a more reliable measure of glycemic control than mean HbA1c in type 2 diabetes mellitus. This study aimed to determine if HbA1c variability is associated with cardiovascular events in type 2 diabetic patients and if different renal functions affect such association. This longitudinal study enrolled 8259 diabetic patients from the Kaohsiung Medical University Research Database in 2009 and were followed-up until 2015. Intra-individual HbA1C variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Several potential mechanisms may link glycemic variability to the occurrence of PAD from a pathophysiological point of view. First, evidence has suggested that oscillating glucose may trigger increases in oxidative stress, endothelial dysfunction or damage, advanced glycation end-products and inflammatory cytokines, resulting in a higher rate of occurrence and acceleration of atherosclerosis independently of sustained hyperglycemia [12][13][14][28][29][30][31][32][33]. Second, A relationship of cardiovascular autonomic dysfunction with atherosclerosis has been observed [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several potential mechanisms may link glycemic variability to the occurrence of PAD from a pathophysiological point of view. First, evidence has suggested that oscillating glucose may trigger increases in oxidative stress, endothelial dysfunction or damage, advanced glycation end-products and inflammatory cytokines, resulting in a higher rate of occurrence and acceleration of atherosclerosis independently of sustained hyperglycemia [12][13][14][28][29][30][31][32][33]. Second, A relationship of cardiovascular autonomic dysfunction with atherosclerosis has been observed [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few studies have investigated the long-term effect of variability in HbA1c [ 29 ]. As a whole, most agree that glycemic variability predicts all-cause mortality, fatal or non-fatal CVD in T2DM [ 30 34 ]. However, there were opposing reports for these outcomes, the RIACE study revealed that HbA1c variability did not have a major effect on macrovascular complications including coronary or cerebrovascular events, myocardial infarction, or stroke [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beck et al proposed that estimation of glycaemic control using HbA1c alone may not be accurate for some patients . Recently, the relationships of HbA1c variability with diabetic complications and mortality in patients with T2D have piqued research interest. A recent study reported that the association of mean HbA1c with all‐cause mortality disappeared after adjustments for HbA1c variability measures, suggesting that HbA1c minimally influences all‐cause mortality.…”
Section: Introductionmentioning
confidence: 99%